Performa Produksi Entog (Cairina moschata) Jantan yang Diberi Ransum Campuran Cacahan Eceng Gondok (Eichhornia crassipes) Kering Jemur - Andre Julkarnaen; Ulfa Indah Laela Rahmah; Dini Widianingrum (Tropical Livestock Science Journal, 2026)
The success of male muscovy cultivation is mainly reflected in production performance. Feed management is a determining factor for this success. This study aims to analyze the effect of feed containing dried water hyacinth (Eichhornia crassipes) on the performance of male Muscovy ducks (Cairina moschata) and determine the optimal inclusion level.The research was conducted experimentally using a Completely Randomized Design (CRD). The treatments applied were P0 (diet + 0% dried water hyacinth), P1 (diet + 5% dried water hyacinth), P2 (diet + 10% dried water hyacinth), and P3 (diet + 15% dried water hyacinth). The variables observed included daily feed intake, average daily gain (ADG), feed efficiency, feed conversion ratio (FCR), and feed cost per gain (FC/G). Data were analyzed using analysis of variance (ANOVA), and if significant differences were found, Duncan’s multiple range test was performed. The results showed that the inclusion of dried water hyacinth had a significant effect on all observed variables. The 10% inclusion level (P2) produced the best results, with higher feed intake, optimal ADG, highest feed efficiency, lowest FCR, and the lowest feed cost per kilogram of weight gain. The results demonstrate that including dried water hyacinth at levels up to 10% improves the performance of male Muscovy ducks and offers a cost-effective feeding strategy.